2022
DOI: 10.3390/biom12111652
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Analysis of NQO1 in Non-Small Cell Lung Cancer Shows Its Expression Is Independent of NRF1 and NRF2 in the Tumor Microenvironment

Abstract: Nuclear factor erythroid 2-related factor 1 (NFE2L1, NRF1) and nuclear factor erythroid 2-related factor 2 (NFE2L2, NRF2) are distinct oxidative stress response transcription factors, both of which have been shown to perform cytoprotective functions, modulating cell stress response and homeostasis. NAD(P)H:quinone oxidoreductase (NQO1) is a mutual downstream antioxidant gene target that catalyzes the two-electron reduction of an array of substrates, protecting against reactive oxygen species (ROS) generation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…In addition, previous studies have also found that NQO1 is upregulated in many human tumors, and high levels of NQO1 are related to poorer patient outcomes ( Awadallah et al, 2008 ). Consistent with previous studies, our findings indicate that most cancers had higher expression levels of NQO1 compared to normal tissue ( Figure 1A ) ( Beaver et al, 2019 ; Kaghazchi et al, 2022 ; Yang et al, 2022 ). The results showed that NQO1 and NRF2 were upregulated in acute lymphoeytic leukemia, cervical squamous cell carcinoma and endocervical adenocarcinoma, cholangiocarcinoma, cholangiocarcinoma, glioblastoma multiforme, glioma, acute myeloid leukemia, brain lower grade glioma, brain lower grade glioma, pancreatic adenocarcinoma, stomach adenocarcinoma, stomach and esophageal carcinoma, stomach and esophageal carcinoma, kidney renal clear cell carcinoma, pan-kidney cohort, kidney renal papillary cell carcinoma, and wilms tumor, suggesting that NQO1 may be involved in the process of tumor development and that the transcription factor NRF2 regulated its expression level.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, previous studies have also found that NQO1 is upregulated in many human tumors, and high levels of NQO1 are related to poorer patient outcomes ( Awadallah et al, 2008 ). Consistent with previous studies, our findings indicate that most cancers had higher expression levels of NQO1 compared to normal tissue ( Figure 1A ) ( Beaver et al, 2019 ; Kaghazchi et al, 2022 ; Yang et al, 2022 ). The results showed that NQO1 and NRF2 were upregulated in acute lymphoeytic leukemia, cervical squamous cell carcinoma and endocervical adenocarcinoma, cholangiocarcinoma, cholangiocarcinoma, glioblastoma multiforme, glioma, acute myeloid leukemia, brain lower grade glioma, brain lower grade glioma, pancreatic adenocarcinoma, stomach adenocarcinoma, stomach and esophageal carcinoma, stomach and esophageal carcinoma, kidney renal clear cell carcinoma, pan-kidney cohort, kidney renal papillary cell carcinoma, and wilms tumor, suggesting that NQO1 may be involved in the process of tumor development and that the transcription factor NRF2 regulated its expression level.…”
Section: Discussionsupporting
confidence: 93%
“…Further analysis of immune infiltration showed that the numbers of M0 macrophages and regulatory T cells were significantly increased in the group with high NQO1 expression, and the immune genes TNFSF9 and LGALS9 were significantly correlated with NQO1. Previous studies have shown that NQO1 plays an important role in specific immune cells, including macrophages, by suppressing Toll-like receptor-mediated innate immune responses [ 28 ], dendritic epidermal T cells [ 29 ], Th17 cells by regulating reactive oxygen species levels [ 30 ], and immune cells within the tumor microenvironment [ 31 ]. Combined with the results of the current study, it can be inferred that NQO1 may affect tumorigenesis and prognosis by influencing the function of immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Zeiss axio scan z1 was utilized to acquire digitized images using fluorescence channels such as Hoechst, FITC and Cy3. Images were then analyzed using HighPlex FL module in Halo AI (Indica Labs®version 3.6.4134) according to published protocol ( 80 ).…”
Section: Methodsmentioning
confidence: 99%